2020
DOI: 10.1016/j.xfre.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Embryos from polycystic ovary syndrome patients with hyperandrogenemia reach morula stage faster than controls

Abstract: Objective: To investigate if patients with polycystic ovary syndrome (PCOS) have altered embryo morphokinetics when compared with controls. Design: Retrospective cohort analysis. Setting: Single academic fertility clinic in a tertiary hospital setting. Patient(s): Age-and body mass index-matched patients who underwent in vitro fertilization diagnosed with PCOS using the Rotterdam criteria. A subanalysis was performed on patients with PCOS with hyperandrogenemia. Sixty-four patients with PCOS were identified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Similarly, A at et al [7] reported comparable oocyte nuclear maturity and embryo grades between PCOS and non-PCOS women during the GnRH antagonist protocol. However, time-lapse studies on embryos development ended up with contradicted results [5,[53][54][55]. The study of Chappell et al [53] showed that embryos from PCOS women displayed a faster growth rate at t7, t8, and t9 compared to controls, while those from hyperandrogenic PCOS showed a faster growth rate at t5, t6, t7, t8, t9, and morula stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, A at et al [7] reported comparable oocyte nuclear maturity and embryo grades between PCOS and non-PCOS women during the GnRH antagonist protocol. However, time-lapse studies on embryos development ended up with contradicted results [5,[53][54][55]. The study of Chappell et al [53] showed that embryos from PCOS women displayed a faster growth rate at t7, t8, and t9 compared to controls, while those from hyperandrogenic PCOS showed a faster growth rate at t5, t6, t7, t8, t9, and morula stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, time-lapse studies on embryos development ended up with contradicted results [5,[53][54][55]. The study of Chappell et al [53] showed that embryos from PCOS women displayed a faster growth rate at t7, t8, and t9 compared to controls, while those from hyperandrogenic PCOS showed a faster growth rate at t5, t6, t7, t8, t9, and morula stage. Similarly, Sundvall et al [54] reported a shorter time to initiate compaction and reach the morula stage; and a shorter duration of the fourth cleavage division in the PCOS embryos compared with the non-PCOS ones, but the kinetic at other time-points were similar.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the specific regulation of Mfn2 expression levels in the sperm of patients might help to alleviate asthenozoospermia and the reduction in progressive sperm motility caused by mitochondrial dysfunction. In females, PCOS is one of the most common diseases that affect women with abnormal endocrine and metabolic conditions that are characterized by ovulatory dysfunction and hyperandrogenemia; the main characteristics are an irregular menstrual cycle and infertility [ 155 , 156 ]. Previous research in PCOS mice showed that mitochondrial fusion/division was disturbed, the levels of ROS were increased, Mfn2 expression was significantly reduced (Fig.…”
Section: Mfns In Reproductive Diseasesmentioning
confidence: 99%
“…We recently showed that embryos from women with hyperandrogenic PCOS grew faster until morula (12). Interestingly, patients with PCOS also showed a higher miscarriage rate, which strongly indicates that a hyperandrogenic ovarian microenvironment could alter fertility and obstetric outcomes (13).…”
mentioning
confidence: 99%